They called him Stonewall : a life of Lieutenant General T. J. Jackson, C.S.A. - Davis, Burke, 1913- (New York, Rinehart, 1954)
The New York Times-bestselling biography of the South's most brilliant and audacious military commander With the exception of Robert E. Lee, no Confederate general was more feared or admired than Thomas "Stonewall" Jackson. Once derisively known as "Tom Fool," Jackson was an innovative battlefield strategist who struck terror in the hearts of Union army commanders and inspired Confederate soldiers to victory after victory in the early days of the Civil War. A fanatically religious man, Jackson prayed at the start and conclusion of every battle--yet showed no mercy when confronting the enemy. Eccentric, enigmatic, and fiercely intelligent, he became the stuff of legend soon after he died from wounds suffered during the Battle of Chancellorsville; his untimely death would help to change the course of the conflict. Based on a wealth of first-person sources, including Jackson's private papers and correspondences, and the memoirs of family, friends, and colleagues, They Called Him Stonewall is a masterful portrait of the man behind the myth
Keywords: Jackson, Stonewall, -- 1824-1863.; Confederate States of America. -- Army -- Biography; Soldiers -- Confederate States of America -- Biography